Femtosecond Laser Machining of Flexible Printed Circuit Boards. Issue 1 (1st January 2022) - Lu, Zheng; Wang, Mingdi; Zhang, Pengcheng; Li, Chuanzhu
Abstract: As the demand grows for high-density electronic components and highly integrated printed circuit boards, femtosecond laser micromachining provides unique opportunities for creating fine conductive tracks and patterns on flexible printed circuit boards (FPCBs) without the use of a mask. Here, the effects of femtosecond laser power and pulse frequency on micromachining depth, surface roughness and copper content of the machined zone were investigated, and optimum laser parameters, i.e., laser power 280 mW and pulse repetition frequency 39.5 kHz, were achieved with the help of a 3D optical profilometer and energy dispersive spectroscopy (EDS). On this basis, a single conductive track with varying widths and two parallel conductive tracks with different widths/spacings were micromachined on FPCBs without noticeable substrate damage. The results indicate that a single conductive line with a feature width as small as 25 µm can be achieved, and two parallel copper tracks can be created with no evidence of the presence of copper residues between the tracks when the pre-defined spacing is no less than 45 µm . In order to achieve high micromachining accuracy, look-up tables that correlate measured widths/spacing of conductive tracks with the pre-defined ones were built.besides, machining conductive tracks with 135 degree corner is possible and by selecting optimized processing parameters. Finally, a driving circuit for a display panel was micromachined on FPCBs using femtosecond laser, and an average micromachining accuracy of 0.67 μm was achieved. This work will be quite useful for creating high density and precision patterns on FPCBs using femtosecond laser.